Characteristics of eye injuries, medical cost and return-to-work status among industrial workers: a retrospective study - Rokiah Omar; Nur Syamilah Anan; Izmel Azim Azri; Chiranjib Majumder; Victor Feizal Knight (BMJ Open)
Objective The aim of this study is to determine the characteristics of eye injuries, medical costs and return-to-work status among industrial workers to provide better vision rehabilitative services.Setting Nationwide data from the Social Security Organisation (SOCSO) of Malaysia.Participants A stratified random sample of workers registered with the SOCSO of Malaysia with documentation of eye injury.Primary and secondary outcome measures Characteristics of eye injuries and medical costs related to eye injury (primary) and return-to-work status (secondary).Results A total of 884 from 8861 case files workplace accidents involving eye injury registered with Social Security Services (SOCSO) were identified. The mean age was 35±10 years and the highest incidence of work-related eye injury occurred in the age group 30–39 years and among Malay ethnics. Males are affected more than females’ workers. The highest cause of eye injury was the impact from a moving object excluding falling objects (89.2%) and anterior segment injuries occurred more than posterior segment injuries. The total direct and Indirect medical cost was RM1 108 098.00 (US$316 599.40) and RM4 150 140.00 (US$1 185 754.20) for 884 cases.Conclusion The majority of workers suffered from the low level of eye injury. A significant relationship was found between the severity of eye injury and employee work status. The indirect cost of medical and vision rehabilitation was higher than the direct cost. Awareness and vision rehabilitation programmes at the workplace need to be addressed for better prevention and rehabilitative service.